BIODIESEL PRODUCTION FROM RUBBER SEEDS {Hevea Brasiliensis) BY IN-SITU TRANSESTERIFICATION METHOD - ABDULKADIR, BASHIR ABUBAKAR (2014)
Biodiesel is mono-alkyl esters ofvegetable oils (both edible and non-edible) oranimal fats. There are two basic methods in which biodiesel can be produced. Firstly, by means of transesterifying oil or fat with an alcohol assisted with an acid or alkali catalyst. Secondly, it can be produced through in-situ transesterification method where the raw material (seeds) can be made to react directly with an alcohol in the present of catalyst. The environmentally friendly nature of biodiesel has made it an attractive alternative that can beused as a renewable fuel in the existing engines. The main objective for this thesis is the production of biodiesel by in-situ transesterification (direct transesterification) method from the seed of rubber tree using KOH as a catalyst. The influence of reaction time, seed sizes, reaction temperature, seed to methanol mass ratio, and seed to catalyst mass ratio on the FAME yield was investigated.